Uveitis, a rare but important complication of adjuvant zoledronic acid for early-stage breast cancer. Issue 4 (24th April 2023) - Chacko, Geena; Kota, Srigowri; Kumar, Shicha; Ohri, Nisha; Omene, Coral; Ganesan, Shridar; Toppmeyer, Deborah L.; George, Mridula A.
Abstract : Bisphosphonates such as zoledronic acid are an important part of adjuvant therapy to reduce the risk of recurrence in early-stage breast cancer. Uveitis remains one of the lesser-known side effects of zoledronic acid; prompt recognition is essential to ensure patients receive appropriate and timely care to help prevent permanent vision loss. We report a case of anterior uveitis in a postmenopausal woman who presented with visual symptoms after receiving the first dose of zoledronic acid. This case report serves to educate and increase awareness of the risk of uveitis in patients who are given zoledronic acid. This is the first and only reported case of zoledronic acid when used in the adjuvant setting for the treatment of breast cancer.